Exogenous Intake of Fluorides in Caries Prevention: Benefits and Risks - Koberová Ivančaková, Romana; Radochová, Vladimíra; Kovácsová, Flóra; Merglová, Vlasta (Acta Medica, 2021)
Caries incidence and prevalence have decreased significantly over the last few decades due to widespread use of fluoride. However, an increase in the prevalence of dental fluorosis has been reported in both fluoridated and non-fluoridated communities. Care must be taken to ensure that a balance between the optimal fluoride preventive effect at the individual and community level and minimal risk of dental fluorosis is maintained. This review describes the main sources of fluoride intake that have been identified: fluoridated drinking water, dietary fluoride supplement, and topical forms comprising toothpastes, rinses, gels and varnishes. The cited data were taken from meta-analytic studies and reports from Cochrane database systematic reviews up to December 2019. Efficiency, but safety, of topically applied fluorides in individual home care is dependent on the degree of compliance of individuals/parents and on the level of competence of providers of preventive counselling. The broad spectrum of these resources allows individualization of fluoride prevention based on risk analysis of caries attack and taking into consideration other preventive measures.
Keywords: potravní doplňky; dentální fluoróza; zubní kaz; služby domácí péče; Dietary Supplements; lokální fluoridy; Dental Caries; Home Care Services; Fluoridation; lidé; Dentifrices; Fluorides, Topical; Mouthwashes; zubní čisticí prostředky; Fluorosis, Dental; Humans; fluoridace; ústní vody